The importance of booklet nursing student in clinical practice - Kegl, Kegl; Harih, Metka; Pajnkihar, Majda; Stričević, Jadranka; Lorber, Mateja; Čučeč Trifković, Klavdija; Donik, Donik (Nursing in the 21st Century, 2012)
THE IMPORTANCE OF BOOKLET NURSING STUDENT IN CLINICAL PRACTICE Aim. Purpose of this study was to determine student opinion about a booklet that is used in clinical practice. The booklet will allow to student coordinators of clinical practice full traceability of student activities in terms of monitoring their progress in professional competence acquisition in all clinical areas of nursing during their studies, while to the students it will serve as a guide for clinical practice and later for the knowledge they acquired. Material and Methodology. The study included 30 part-time and 40 full-time students in the second year of the undergraduate study program in nursing care (first degree) in the academic year 2010/2011, who participated in clinical practice at the Pediatric Clinic of the University Medical Center Maribor. We used a quantitative research approach and the method of interview. The data were statistically analyzed using software SPSS 17.0. Results. The results showed that students of nursing care are satisfied with a booklet of activities in nursing, since they represent an accurate and easy-to-understand guide to performing nursing interventions and also self-assessment at the end of clinical practice. Students are of the opinion that the main characteristic of a good guide book is usability in all areas of clinical practice; on the other hand, they want a guide book that would be more specific for individual clinical fields. Conclusions. The booklet of nursing activities will allow both students and coordinator the complete controllability in terms of tracking professional advancement of a student during the studies in all clinical fields and at the end of studies will serve as proof of practical training of students at our faculty.